Application of The Fuel Estimation Simulator (The Bung Tomo Training Ship) - Tri Cahyadi; Agus Dina Mirianto; Fazri Hermanto (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Developing new routes in the shipping business, the calculation uses the formula determined by the Minister of Transportation No.  KM.  58 of 2003. However, this manual calculation takes a long time, and the possibility of human error is large.  So, we need a more effective and efficient way to calculate the fuel needed to cover a certain distance.  In this study, a simulator was developed that uses the spherical triangle concept to determine the distance and direction of the ship and then integrates it with the formula to get the results of the fuel calculation.  From the results of trials using the Bung Tomo Training Ship, the results of calculations are faster and more accurate.  The simulator positively affects cadets when applied in applied mathematics classes (85% through response questionnaire results and 87% competency test).